2023
DOI: 10.3389/fmicb.2023.1130677
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of dried blood spot-measured anti-SARS-CoV2 Spike IgG in mRNA-vaccinated healthcare workers

Abstract: IntroductionOne of the major criticisms facing the research community during SARS-CoV2 pandemic was the lack of large-scale, longitudinal data on the efficacy of the SARS-CoV2 mRNA vaccines. Currently, even if COVID-19 antiviral treatments have been authorized by European Medicine Agency, prevention through approved specific vaccines is the best approach available in order to contain the ongoing pandemic.ObjectivesHere, we studied the antibody kinetic over a one-year period from vaccination with the Pfizer-Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Booster doses have been recommended to HCWs with the expectation that it will maintain the benefits of vaccination and reduce absenteeism. Some studies have shown booster doses inducing a significant and sustained increase in anti-SP IgG titers ( 18 ) while others have found a more short-lived impact ( 19 ). Nonetheless, there is a growing body of evidence on the side effects of COVID-19 vaccines and resulting time off work ( 20–22 ), which should not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Booster doses have been recommended to HCWs with the expectation that it will maintain the benefits of vaccination and reduce absenteeism. Some studies have shown booster doses inducing a significant and sustained increase in anti-SP IgG titers ( 18 ) while others have found a more short-lived impact ( 19 ). Nonetheless, there is a growing body of evidence on the side effects of COVID-19 vaccines and resulting time off work ( 20–22 ), which should not be ignored.…”
Section: Introductionmentioning
confidence: 99%